2008
DOI: 10.1007/s00268-007-9387-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Cushing’s Syndrome: An Historical Review and Recent Ten‐year Experience

Abstract: Surgery for CS is highly successful for pituitary-dependent CS and most ACTH-independent adrenal causes. Bilateral total adrenalectomy can also provide effective palliation from the ravages of hypercortisolism in patients with ectopic ACTH syndrome and for those who have failed transsphenoidal surgery. Unfortunately, to date, adrenocortical carcinomas are rarely cured. Future successes with this disease will likely depend on a better understanding of tumor biology, more effective adjuvant therapies and earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
16

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 136 publications
(236 reference statements)
1
32
0
16
Order By: Relevance
“…In a series of 18 patients with EC who underwent bilateral adrenalectomy, O'Riordain et al (26) found 5-year survival probability of 39%, with 73% of deaths related directly to metastatic malignant disease. Porterfield et al (25), in a group of 35 subjects who also had bilateral adrenalectomy, reported 5-year survival probability of 51.3%. In a series of 90 patients with EC followed up for a median period of 26 months, Ilias et al (27) demonstrated that subjects with an unknown/occult source survived longer compared with those with an identified tumour and that amongst those with identified tumour, patients with pulmonary EC (excluding small cell lung cancer) survived longest.…”
Section: Discussionmentioning
confidence: 97%
“…In a series of 18 patients with EC who underwent bilateral adrenalectomy, O'Riordain et al (26) found 5-year survival probability of 39%, with 73% of deaths related directly to metastatic malignant disease. Porterfield et al (25), in a group of 35 subjects who also had bilateral adrenalectomy, reported 5-year survival probability of 51.3%. In a series of 90 patients with EC followed up for a median period of 26 months, Ilias et al (27) demonstrated that subjects with an unknown/occult source survived longer compared with those with an identified tumour and that amongst those with identified tumour, patients with pulmonary EC (excluding small cell lung cancer) survived longest.…”
Section: Discussionmentioning
confidence: 97%
“…The success rate of 67% with first TSS in our series is comparable to that reported in the literature. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The main weakness of this study is that in about 8% of the patients the source of ACTH escaped detection. This is possibly due to non-availability of some essential investigations like CRH stimulated IPSS for ACTH determination.…”
Section: Discussionmentioning
confidence: 99%
“…19 The measuring range of cortisol assay was 0.018 μg/dL to 63.4 μg/dL with inter-assay and intra-assay CV <5.6%. Plasma ACTH was determined using two monoclonal antibodies specific for ACTH (ACTH: 9-12 & ACTH: [36][37][38][39]. The measuring range of the ACTH assay was 1-2000 pg/ml with inter-assay and intra-assay CV <6%.…”
mentioning
confidence: 99%
“…Although generally out of favour (12), laparoscopic TBA can be useful when a corticotrophinoma is undetectable, surgically unresectable or there is recurrence following TSS. In these cases, TBA offers 85-100% success rate in controlling hypercortisolaemia (3,11) and is particularly useful in patients with life-threatening manifestations of hypercortisolism (13).…”
Section: Introductionmentioning
confidence: 99%